2017
DOI: 10.3141/2609-04
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Principles of Energy Exchanges to the Rail Freight Sector

Abstract: One of the major goals of the European Union's transport policy is to increase the market share of rail freight transports. With the Internet, globalization, and just-in-time production, the future of freight transport has moved to high-value and lightweight goods. Rail freight has had difficulty entering this market. Thus, a multipronged strategy is required for improving the rail freight market in which freight is consolidated and transported in Europe by encouraging new players to enter the market. A key pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The first conclusion is that the earlier specified conceptual framework OEMF [10] appears very supportive in evaluating and comparing online exchanges in the freight transportation industry. The consequent use of the elaborated KPIs support the data collection and the evidence based in-depth assessment of various practices of online exchanges in freight transport.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The first conclusion is that the earlier specified conceptual framework OEMF [10] appears very supportive in evaluating and comparing online exchanges in the freight transportation industry. The consequent use of the elaborated KPIs support the data collection and the evidence based in-depth assessment of various practices of online exchanges in freight transport.…”
Section: Discussionmentioning
confidence: 88%
“…The framework was based on a study of characteristics of various network industries (capacity management, transport services, infrastructural and market conditions, regulation, etc.) (see also [10]). Although the analysis focused on the coping with regulatory topics that can possibly improve rail freight integration in multimodal freight transport, among others it was also concluded that for multimodality the standardization of products is essential.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Regarding freight transport, nowadays hundreds of road FTEs are used within Europe (Jain & Bruckmann, 2017). Recently launched exchanges additionally offer transport of partial loads on their platforms.…”
Section: Introductionmentioning
confidence: 99%